COMPARING CULTURAL PRACTICES AND MAKING SUGGESTIONS FOR EFFECTIVE CROSS-CULTURAL COMMUNICATION - Sotvoldiyeva Mastura Yahyobek qizi; Turaxon Abduraxmonov Saydullayevich (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Annotation: This thesis explores the diversity of cultural practices across different societies and examines their impact on communication and social interaction. Cultural practices, including traditions, values, communication styles, religion, and everyday behaviors, differ significantly between Western and Eastern cultures. The study provides a comparative analysis of these differences and highlights their influence on interpersonal relationships. Furthermore, the article identifies major challenges in cross-cultural communication, such as stereotypes, ethnocentrism, language barriers, and misinterpretation of non-verbal cues. Special attention is given to the role of globalization in increasing intercultural interactions. The thesis also offers practical recommendations for improving cross-cultural communication, including enhancing cultural awareness, developing empathy, improving language skills, and promoting intercultural education. The findings emphasize that effective communication in a multicultural environment requires respect, tolerance, and adaptability.